Pemanfaatan Teknologi Artificial Intelligence (ChatGPT), Googlesheet dan Video untuk Peningkatan Kapasitas Digital UMKM Desa Kroya - Shinta Romadhona; Linahtadiya Andiani; Eko Fajar Cahyadi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This community service activity aims to identify the level of understanding, utilization, and perceived benefits of Artificial Intelligence technology, specifically ChatGPT, Google Sheets, and basic video content creation, for Small, and Medium Enterprises (SMEs) in Kroya Village. The program was designed as a digital capacity-building initiative to support SMEs in improving marketing effectiveness, administrative efficiency, and creative content production. A quantitative descriptive approach was employed using a survey instrument consisting of 15 Likert-scale questions distributed to 25 SME participants. The survey measured digital literacy, perceived usefulness, implementation readiness, and training relevance. The results show that the average response score of participants ranged between 3.8 and 4.6, indicating a high level of acceptance and positive perception toward AI-based tools. The highest average scores were observed in aspects related to marketing content creation and efficiency improvement. These findings demonstrate that ChatGPT and supporting digital tools are highly relevant for SME empowerment, particularly in strengthening promotional strategies and operational efficiency. The activity concludes that structured training in AI-based digital tools can significantly enhance SME readiness for digital transformation.